HIV-related cognitive disorders in children in Kinshasa (Democratic Republic of Congo) - Esther Maboso Ekolo; Aimée Masaya Mupuala; Joseph Mabiala Bodi; Adolphine Nkuadiolandu; Pierre Manyanga Tshibasu (BMC, 2024)
Abstract Objectives HIV-infected individuals are at increased risk of neurocognitive disorders compared with the general population. Studies suggest that, despite the combination of antiretroviral drugs, HIV infection causes immune activation leading to significant neural damage; however, there is little data on HIV-infected young people in our country. Methodology This is a comparative cross-sectional study conducted between November 2020 and March 2021 on two hundred and sixteen children aged 6-15 years, including 106 HIV-positive children and 108 healthy children. Cognitive performance was assessed using the Differential Ability Scale Second Edition (DAS-II). Results HIV-infected children showed lower cognitive scores than control children in the subtest group of verbal ability (82.1% vs. 43.5%); non-verbal ability (84.9% vs. 45.4%); spatial ability (79.2% vs. 21.3%) and generall conceptual ability (GCA) (88.7% vs. 43.5%). The children in the control group had significantly higher ability scores in the diagnostic tests and in school achievement, and the difference was statistically significant. Conclusion Cognitive impairment remains a significant complication in HIV-positive children, as suggested by low cognitive scores in more than half of our participants. This is an unresolved issue with implications for survival, quality of life and daily functioning in these children. It is important that clinicians are able to identify and manage these cognitive deficits.